2014
DOI: 10.1177/1475240914540119
|View full text |Cite
|
Sign up to set email alerts
|

Are Chinese university students more likely to exhibit a Surface approach to learning than other international students in Finland?

Abstract: This article is based on a study which investigated whether Chinese international students at a university in Finland are more likely to rely on a Surface approach to learning and dismiss a Deep approach than are other international students in the same university educational context. In responding to a survey, students' scores with respect to the Deep approach and Organized Studying did not significantly differ between the groups. However, the Chinese students appeared slightly to exhibit the Surface approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…Our study results demonstrated that both the CCT students and the freshmen entrants adopted deep and organised approaches to learning (p = 0.76). This echoes the finding of Sakurai and colleagues [41], that Chinese students use deep and organised studying approaches is much the same ways their international counterparts do. As the students in both groups favour deep approaches to learning, the CCT students scored significantly higher than the freshmen entrants on surface approaches (p < 0.0001).…”
Section: Approaches To Learningsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study results demonstrated that both the CCT students and the freshmen entrants adopted deep and organised approaches to learning (p = 0.76). This echoes the finding of Sakurai and colleagues [41], that Chinese students use deep and organised studying approaches is much the same ways their international counterparts do. As the students in both groups favour deep approaches to learning, the CCT students scored significantly higher than the freshmen entrants on surface approaches (p < 0.0001).…”
Section: Approaches To Learningsupporting
confidence: 78%
“…Previous research on students' approaches to learning has found that there are differences the learning approaches of eastern and western students. Sakurai and colleagues [41] and Zhu and colleagues [42] indicated that eastern students are better adapted to surface approaches than western students. Some studies in Japan and China have found that their students employ both surface and deep approaches to learning simultaneously or in series [30][31][32][33][34]43].…”
Section: Approaches To Learningmentioning
confidence: 99%
“…There are stereotypes existing in the literature about Chinese students as rote learners, passive knowledge receivers and accumulators (Ho, 1994;Salili, 1996). If teachers accept the stereotyped view, they may implement their pedagogical practices according to their beliefs about students' learning preferences (Dasari, 2009;Sakurai et al, 2014). Further, it is important that teachers in HEIs review their own understanding of their students based on empirical evidences so that they can develop more effective blended learning strategies for students coming from the Confucian culture.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is important that teachers in HEIs review their own understanding of their students based on empirical evidences so that they can develop more effective blended learning strategies for students coming from the Confucian culture. In Sakurai et al's (2014) view, "teachers' biased expectations could result in an undesired pedagogical design, which may lead to a poor quality of student learning" (p. 137). This study revealed that high-quality learning virtues, such as resolve, diligence and obedience, are deeply embedded in Hong Kong Chinese learners.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been argued that the Western view of the role that rote learning plays within a 'Chinese approach' to learning is partial and it is a mistake to see it as a negative (Tan, 2011;Tweed & Lehman, 2002). Furthermore, the tendency of Chinese students to exhibit study characteristics associated with surface learning is not incompatible with those same students adopting deep approaches to study (Sakurai et al, 2014).…”
Section: Preparation For Higher Educationmentioning
confidence: 99%